2-[(2-Chlorophenyl)iminomethyl]-4,6-dimethyl-quinoline - Öztürk, S; Akkurt, M; Aygün, M; Aydogan, F (INT UNION CRYSTALLOGRAPHY, 2001)
The molecule of the title compound, C18H15ClN2, is not planar. The dihedral angle between the quinoline and phenyl rings is 116.2 (1)degrees. Bond lengths and angles are normal.
Keywords: CRYSTAL-STRUCTURE; Crystallography